2015
DOI: 10.1177/0960327115577542
|View full text |Cite
|
Sign up to set email alerts
|

Thrombolytic therapy in a patient with inferolateral myocardial infarction after carbon monoxide poisoning

Abstract: Introduction: ST segment elevation myocardial infarction (STEMI) due to coronary artery occlusion caused by intracoronary thrombosis in the setting of acute carbon monoxide (CO) poisoning is a very rare presentation. We present a case of intracoronary large and mobile thrombus formation after CO poisoning. Case presentation: A previously healthy 50-year-old woman was referred for CO poisoning. She had ches… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…One study showed that levosimendan can reverse stunned myocardium (117). Although no one has studied empiric antiplatelet or anticoagulation in CO poisoning, this could be an area of further study, especially in high-risk patients (50,119).…”
Section: Alternative Strategiesmentioning
confidence: 99%
“…One study showed that levosimendan can reverse stunned myocardium (117). Although no one has studied empiric antiplatelet or anticoagulation in CO poisoning, this could be an area of further study, especially in high-risk patients (50,119).…”
Section: Alternative Strategiesmentioning
confidence: 99%
“…Venous and arterial thromboembolic events in the context of CO poisoning are not uncommon. Cases of venous thrombosis, pulmonary embolism, ischemic stroke, atrial thrombus, and intracoronary thrombus have been reported in patients exposed to an excess of CO . The rate of clot formation and the clot progression itself was shown to be significantly increased after brief CO exposure .…”
Section: Discussionmentioning
confidence: 99%
“…Six articles were found describing myocardial injury post‐CO poisoning that is thought to be caused by an acute intracoronary thrombus . Unlu et al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations